Poly-optimization of parameters of fractional-order power system stabilizers operating in the power system - Nocoń, Adam; Paszek, Stefan; Pruski, Piotr (Archives of Control Sciences, 2026)
This paper presents a new fractional-order power system stabilizer, PSS3B_FRAC, developed as a modification of the standard PSS3B stabilizer. Optimization-based procedures are applied to determine stabilizer parameters in single-machine and multi-machine systems. The results demonstrate that introducing fractional-order differentiation improves damping of electromechanical swings while maintaining acceptable voltage regulation. The study is conducted in three stages: (1) single-objective optimization in single-machine systems, (2) single-objective optimization in a 7-machine CIGRE system, and (3) poly-optimization in the same system.